Evaluation of Long-Term Silicone Hydrogel Use on Ocular Surface Inflammation and Tear Function in Patients With and Without Meibomian Gland Dysfunction. Issue 1 (January 2019) - Yucekul, Burcu; Mocan, Mehmet C.; Kocabeyoglu, Sibel; Tan, Cagman; Irkec, Murat
Abstract : Objectives: To determine whether silicone hydrogel (SH) contact lens (CL) use, with or without meibomian gland dysfunction (MGD), promotes ocular surface inflammation. Methods: Subjects wearing SH-CL for at least 6 months who also had coexisting MGD (group 1, n=20), SH-CL users who did not have MGD (group 2, n=20), patients who had MGD but did not use CL (group 3, n=20), and healthy CL-naive individuals with no known systemic or ocular diseases (group 4, n=20) were included in this cross-sectional, single-center study. All subjects underwent tear function tests consisting of tear break-up time (tBUT), ocular surface staining, Schirmer test, and the Ocular Surface Disease Index (OSDI) questionnaire, as well as determination of tear IL-1RA, IL-1β, IL-2, IL-2R, IL-4, IL-5, IL-6, IL-7, IL-8, IL-10, IL-12, IL-13, IL-15, IL-17, IFN-α, IFN-γ, TNF-α, granulocyte-macrophage colony-stimulating factor, IP-10, monokine induced by gamma interferon, RANTES, eotaxin, MIP-1α, MIP-1β, and MCP-1 levels using Luminex multicytokine immunobead assay. Intergroup comparisons were made using one-way analysis of variance or Kruskal–Wallis test. Results: The tBUT was lower ( P =0.048) and ocular surface staining ( P =0.032) as well as OSDI scores ( P =0.001) were higher in group 1 but not in groups 2 or 3 when compared with those in the control group. Tear cytokine levels were similar across all groups. None of the tear cytokine levels were elevated in CL wearers (groups 1 and 2) or those with MGD (groups 1 and 3) as compared to those in control subjects. Conclusion: Silicone hydrogel contact lens use with concomitant MGD is not associated with cytokine-driven ocular surface inflammation but may impact tear function leading to dry eye symptoms.